Rethinking college admissions : research-based practice and policy - Poon, OiYan; Bastedo, Michael N. (Cambridge, MA: Harvard Education Press, 2022)
Rethinking College Admissions probes the many facets of higher education admissions and translates research-backed insights into actionable strategies for innovative, equitable admissions practices. Edited by scholars OiYan A. Poon and Michael N. Bastedo, this collection gives readers an evidence-based understanding of postsecondary admissions practices and structures, exploring many factors that affect college access and educational equity in the United States. A must-read for practitioners, policy makers, and anyone interested in gaining a better understanding of postsecondary admissions structures, including K-12 educators and counselors, advocacy groups, and students, this work supports data-informed approaches to higher education admissions.
Includes index and bibliographical references and index.
Buku bacaan asas fakulti
Keywords: Universities and colleges -- United States -- Admission